Seroprevalence of Hepatitis C Virus in Thalassemic Patients (Journal of Dhaka Medical College, 2010)
Hepatitis C virus is one of the leading causes of liver disease and represents a major public health problem. It is a common cause of cirrhosis and hepatocellular carcinoma (HCC) as well as the most common reason for liver transplantation. This cross sectional study was carried out during the period of April 2007 to April 2008 among thalassemic patients with history of multiple blood transfusion (>20 units). Total 200 thalassemic patients from Thalassemia Samity Hospital, Green Road, Bangladesh Thalassemia Foundation, Dhanmondi, and from Department of Transfusion Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka were included in the study.After taking detailed history and clinical examination , 0.3 ml of venous blood was collected from each patient and tested for anti HCV by commercial kit. Positive cases were confirmed by ELISA method. Among 200 patients majority (68.5%) were below age of 20 years with a male to female ratio of 1.7:1,16.5% were found to have anti HCV positive. Anti HCV positivity increased with duration of exposure and number of blood transfusion., 22.9% of patients who had duration of exposure for more than 10 years and 36.4% having blood transfusion more than 40 units were positive for anti HCV. Key words: Seroprevalence; hepatitis C virus; thalassemia. DOI: 10.3329/jdmc.v18i2.6269 J Dhaka Med Coll. 2009; 18(2) : 115- 119